SCIENTIFIC PROJECT ACTIVITY AS A BACKGROUND FOR THE FORMATION OF PROFESSIONAL COMPETENCIES OF APPLICANTS OF HIGHER EDUCATION IN ELECTRICAL ENGINEERING - SHVEDCHYKOVA, IRYNA; SOLOSHYCH, IRYNA; SOLOSHYCH, SERHII (Technologies and Engineering, 2022)
Purpose. Determination of the role of scientific project activity in the formation of professional competencies of applicants for higher education in the field of electrical engineering. Methodology. The method of scientific projects is used to form the professional competencies of applicants for higher education in the specialty “Electricity, electrical engineering and electromechanics”. Findings. The implementation of project scientific activities using the base of engineering and scientific projects to improve energy efficiency motivates applicants for higher education to acquire new knowledge, creates the preconditions for the development and implementation of a modern educational program in the field of electrical engineering, contributes to the integration of a new structure into the university system – an energy-innovative hub of knowledge. Originality. In the work design methods and teaching technologies in the field of electrical engineering were further developed, which provide the use of the university base of scientific and engineering projects on energy efficiency and participation in the implementation of projects of applicants for higher education, which allows to form professional (scientific-research) competencies of applicants and to develop modern educational program. Practical value. The research results can be used to update educational programs in electrical engineering and to support the development of energy efficiency at the university when creating an energy-innovative knowledge hub that will allow organizing a complex interaction of the components “education – science (innovation) – business (entrepreneurship) – state”.